Kompartemen Sindrom Ekstremitas Bawah : Diagnosis, Anatomi dan Tatalaksana - Fuad Iqbal Elka Putra; Hanifah Hanum (Medula, 2023)
Abstract Acute compartment syndrome (ACS) is an orthopaedic emergency that can threaten life and limb. A comprehensive understanding of anatomy, along with proper diagnosis and treatment, plays a crucial role in preventing lower limb ischemia. We conducted an updated review of the literature using digital databases such as PubMed, Springer Link, and Science Direct. A clinical diagnosis of compartment syndrome must be followed by surgical decompression. Clinical signs of ACS include the 6 P’s: pain, poikilothermia, pallor, paresthesia, pulselessness, and paralysis. This literature review revealed that some studies showed fasciotomy is an emergency surgical procedure performed to decompress a compartment. The most common and validated method to measure limb intracompartment pressure (ICP) is by using the handheld Stryker Intra-Compartmental Pressure (STIC) Monitor System. Lower leg compartment divided into anterior, lateral, superficial posterior and deep posterior compartment, inside of compartment there are muscle, nerve, artery and vein. After diagnosis compartment syndrome we should continue to surgical decompression by fasciotomy in two methode medial incision (deep and superficial posterior compartment) and lateral incision (anterior and lateral compartments). As a conclusion early recognition and diagnosis of conditions of compartment syndrome are essential in preventing lower limb ischemia. Keywords: acute compartment syndrome, intracompartmental pressure, lower extremity